Taxpayers’ Trust on Rural and Urban Lands and Building Tax Online Payment Using QRIS - Wulansari, Kristin; Kalangit, Della Olivia Caterina; Satryawati, Satryawati; Kawuryan, Renita (Interdisciplinary Social Studies, 2022)
Background: Quick Response Code Indonesian Standard or commonly abbreviated as QRIS is the unification of various QR types from various Payment System Service Providers (PJSP) using a QR Code, QRIS can accept all payments from anywhere, both Bank and Non-Bank (Fintech), The Regional Revenue Service of Samarinda City applies QRIS as one of the means of payment of The Rural and Urban Land and Building Tax. Aim: This study was conducted to measure the confidence of taxpayers in accepting QRIS for The Rural and Urban Land and Building Tax Payment. The model used in this study is the Technology Acceptance Model (TAM) with the addition of the trust variable. Method: The data used are primary data obtained through distributing questionnaires to 180 respondents using QRIS as a means of paying The Rural and Urban Land and Building Tax in Samarinda City, where the implementation of the results of the research on the main respondents aged 25-45 years. There are five variables used in this study, namely perceived usefulness, perceived ease of use, intention to use, application use, and trust. Findings: The results obtained are Perceived Usefulness and Perceived Ease of Use have a significant influence on Attitude Toward Using. The Attitude Toward Using variable has a significant effect on Behavioral Intention To Use, and the Trust variable has a significant influence on Perceived Usefulness, Perceived Ease of Use, and Behavior Intention to Use. This means that Trust affects the use of QRIS every day and in the future.